Construcción de un bentilador axial para el laboratorío de la facultad de Ingeniería - Inca Pérez, Miguel Ángel (2011)
Students and teachers who use the Unit Operations Laboratory have the need to know, to experience and handling each of the existing machine there for, this reason, and feeling the great importance of ventilation systems in the industry we have seen the need to build an axial fan. The equipment allows the study of the ventilation process this is achieved by a five-blade rotor phones, integral with a drive shaft driven by a three phase motor that drives air in a straight line with helical outflow. In order to give to the student skill acquisition and skills in handling of the equipment and they are involved directly in the production processes of the industry.